2017
DOI: 10.1007/s00709-017-1130-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the fruit structure and the location and content of bioactive substances in Viburnum opulus and Viburnum lantana fruits

Abstract: Many Viburnum species are popular ornamental shrubs and, simultaneously, highly valued medicinal plants as a source of many bioactive compounds, including antioxidants. Viburnum bark, flowers, and fruits are widely used in traditional and folk medicine, and the fruits of some species are used as cooking ingredients. The knowledge of the microstructure of Viburnum fruits and the accumulation sites of bioactive substances in these organs is rather poor. Comparative analyses of the microstructure of ripe Viburnum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 75 publications
(72 reference statements)
1
20
0
Order By: Relevance
“…Some previous studies showed that the existence of phytochemical compounds in plants are influenced by some factors such as adaption to the environmental factor and the growth of each individual species. According to [11], the distribution of alkaloid content in various species of plant [12] stated that tannins are mostly accumulated in the pericarp and mesocarp of Viburnum opulus and Viburnum lantana. Moreover, according to [13], there are some factors which influence the composition and distribution of saponins in plants, for example, the protection level against predator attacks and the changes of the environment; the protection on the reproductive organs during the growth of fruit and the formation of tubers.…”
Section: Phytochemical Contentsmentioning
confidence: 99%
“…Some previous studies showed that the existence of phytochemical compounds in plants are influenced by some factors such as adaption to the environmental factor and the growth of each individual species. According to [11], the distribution of alkaloid content in various species of plant [12] stated that tannins are mostly accumulated in the pericarp and mesocarp of Viburnum opulus and Viburnum lantana. Moreover, according to [13], there are some factors which influence the composition and distribution of saponins in plants, for example, the protection level against predator attacks and the changes of the environment; the protection on the reproductive organs during the growth of fruit and the formation of tubers.…”
Section: Phytochemical Contentsmentioning
confidence: 99%
“…This is very important because the hallmark of modern society is healthy food, the leading role in which belongs to consumption of food rich in vitamins, macro and microelements composition. Such requirements are met by leaves, fruits and seeds of the snowball tree (Karaçelik et al, 2015;Goszcz et al, 2017;Konarska & Domaciuk, 2018;Kozlowska et al, 2018). Studying and conducting comparative assessment of differences in degustation evaluation of fruits of the snowball tree are important for developing features of its processing products.…”
Section: Discussionmentioning
confidence: 99%
“…Česonienė et al (2010), Shchetilina et al (2016) studied a broad range of biologically active substances, including antioxidants, providing new opportunities of using raw materials from the snowball tree in production of pharmaceuticals. According to the literature data Konarska & Domaciuk (2018), sugars are the main source of energy necessary for different physiological processes in the cell. They determine nutritional characteristics of both fresh fruits of the snowball tree and products of their processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations